Colloidal gold-based indirect competitive immunochromatographic assay for rapid detection of bioactive isoflavone glycosides daidzin and genistin in soy products. (1st March 2016) - Sakamoto, Seiichi; Yusakul, Gorawit; Pongkitwitoon, Benyakan; Tanaka, Hiroyuki; Morimoto, Satoshi
Highlights: One-step immunochromatographic assay (ICA) was developed for soy isoflavone glycosides. Limit of detection of ICA system developed is ∼125 ng mL −1 . Semi-quantitative analysis of DZ and GEN can be also performed by ICA developed. Abstract: Daidzin (DZ) and genistin (GEN) are two major soy isoflavone glycosides isolated from soybeans. Soy products containing isoflavones have recently been widely accepted for commercial use. However, the Japanese Government has suggested that soy isoflavone intake should be limited because of their estrogenic effects due to their interactions with estrogen receptors. In this study, we established a one-step indirect competitive immunochromatographic assay (ICA) for rapid and sensitive detection of total isoflavone glycosides (DZ and GEN) using gold nanoparticles conjugated with a monoclonal antibody against DZ. This assay was able to be completed in 15 min following the immersion of a test strip in an analyte solution. Furthermore, the limit of detection for the total amount of isoflavone glycosides was ∼125 ng mL −1 . Considering that the major soy isoflavone glycosides found in soy products are DZ and GEN, this study demonstrates the potential use of ICA for the assessments of over consumption of isoflavones in soy supplements and foods, which would increase the safe dietary intake of soy products.